Systematic Review on Oral Health Knowledge, Practice and Attitude In Pakistan - Karim, Anum; Syed, Haniya Zehra; Kabir, Russell (Asian Journal of Public Health and Nursing, 2024)
Background: The term "oral health" describes the state of the mouth's defence against ailments that affect the oral cavity, such as tooth decay, periodontal disease, cancer of the mouth and throat, facial discomfort, and ulcers. Oral cleanliness, tobacco usage, alcohol consumption, and general diet are the main contributors to oral health issues and illnesses. The most significant advantage of maintaining proper dental hygiene is the prevention of diseases. In Pakistan, dental health is not given much priority. The aim of this systematic review is to thoroughly examine and summaries the body of research on Pakistani people's attitudes, practices, and knowledge on oral health. The study aims to identify knowledge gaps, offer a thorough review of the existing situation regarding oral health awareness, habits, and attitudes, and indicate possible areas for development. Methods: This thorough systematic review, which adheres closely to PRISMA principles, examines all cross-sectional studies examining the gaps in oral health knowledge, practice, and attitude in Pakistan. Several databases such as Medline, ProQuest Central, Web of Science, and Scopus were used and past and current reviews on the same subject were looked in the Cochrane Database of Systematic Reviews. Selected papers were meta-synthesized to produce results that were both statistically sound and strong. Results: The findings reveal that there are differences in the population's knowledge about oral health, certain groups with low socio-economic status showing less understanding of preventive and good oral hygiene habits. Conclusion: This review highlights the need for all-encompassing strategies that account for differences in geography, culture, and socioeconomic disparities by placing the findings in a broader literary context. To improve oral health outcomes across the country, specific public health campaigns, educational programmes, and policy measures are crucial given the knowledge gaps and practice discrepancies that have been discovered. By addressing these problems, we can improve people's general health and lessen the prevalence of oral disorders in Pakistan.